Suggestions on converting ammonium nitrate manufacturing capacity for production of porous ammonium nitrates and ammonium nitrate with fillers - A. L. Taran; N. V. Konochova; V. E. Kuchinsky; Yu. A. Taran; D. S. Yakovlev; D. A. Kuzina; I. P. Titova (Тонкие химические технологии, 2009)
The way of increasing competitiveness of the existing domestic factories manufacturing nitrogen containing chemical fertilizers is suggested. The approach involves minimal retooling of the existing equipment which will allow production of the ammonium nitrates containing fillers (e.g., manufacturing of ASN, CAN, AC, NP, NK fertilizers) as well as manufacturing of porous ammonium nitrate (PAN).